Trends in Pop-Up Book Media Development for Elementary Science Education: A Systematic Review (2020-2025) - Ari Ferdianto; Nuni Widiarti; Bambang Subali (Papanda Publisher, 2026)
This study analyzes research trends in Pop-Up Book media development for elementary school science education from 2020 to 2025 using a Systematic Literature Review based on the PRISMA framework. A total of 138 articles met the eligibility criteria, and a subset of studies focusing on development-oriented research was examined to identify dominant patterns and approaches. The findings indicate that Pop-Up Book development commonly applies instructional design models such as ADDIE and Borg & Gall, frequently integrated with student-centered learning approaches including Project-Based Learning, Problem-Based Learning, and scientific literacy frameworks. Across the reviewed studies, Pop-Up Books are consistently reported to support student motivation, conceptual understanding, and active participation, with outcomes primarily measured through pre–post learning gains and qualitative classroom observations. Recent research also demonstrates a shift from manually designed Pop-Up Books toward digital and hybrid formats incorporating interactive and augmented elements. Overall, the review highlights the growing role of Pop-Up Books as adaptive and contextually meaningful learning media aligned with 21st-century elementary science education.